Cross-beta nanostructures based on dinaphthylalanine Gd-conjugates loaded with doxorubicin - Carlo Diaferia; Eliana Gianolio; Teresa Sibillano; Flavia Anna Mercurio; Marilisa Leone; Cinzia Giannini; Nicole Balasco; Luigi Vitagliano; Giancarlo Morelli; Antonella Accardo (Scientific Reports, 2017)
Abstract Very recently we proposed novel di- and tetra-phenylalanine peptides derivatized with gadolinium complexes as potentials supramolecular diagnostic agents for applications in MRI (Magnetic Resonance Imaging). It was observed that in very short FF dipeptide building blocks, the propensity to aggregate decreases significantly after modification with bulky moiety such as Gd-complexes, thus limiting their potential as CAs. We hypothesized that the replacement of the Phe side chain with more extended aromatic groups could improve the self-assembling. Here we describe the synthesis, structural and relaxometric behavior of a novel water soluble self-assembled peptide CA based on 2-naphthylalanine (2Nal). The peptide conjugate Gd-DOTA-L6-(2Nal)2 is able to self-assemble in long fibrillary nanostructures in water solution (up to 1.0 mg/mL). CD and FTIR spectroscopies indicate a β sheet secondary structure with an antiparallel orientation of single strands. All data are in good agreement with WAXS and SAXS characterizations that show the typical “cross-β pattern” for fibrils at the solid state. Molecular modeling indicates the three-dimensional structure of the peptide spine of aggregates is essentially constituted by extended β-sheet motifs stabilized by hydrogen bonds and hydrophobic interactions. The high relaxivity of nanoaggregates (12.3 mM−1 s−1 at 20 MHz) and their capability to encapsulate doxorubicin suggest their potential application as supramolecular theranostic agents.